THARIQAH MUBASYARAH PADA PEMBELAJARAN BAHASA ARAB KELAS VIII MADRASAH TSANAWIYAH MA’HAD AL-ZAYTUN TAHUN 2024 - Izzah Khairunnissa (CV. Denasya Smart Publisher, 2025)
Learning Methods are an important component in learning, Teachers have an important role in teaching and learning activities, one of the methods that can be applied in learning Arabic is the Mubasyarah Method. The objectives of this study are (a) to determine the effect of Tariqah Mubasyarah on Arabic language learning (b) to find a solution if Tariqah Mubasyarah has no effect on Arabic language learning. The method that researchers use in this study is a Quantitative Approach, type of research Quasi Experiment, with the type of design one group pretest-posttest design. Data collection techniques using observation and tests. The research subjects consisted of 30 students of class VIII Mts Ma'had Al-Zaytun. Data analysis carried out is descriptive analysis and inferential analysis, with Hypothesis Test in the form of Wilcoxon Test. Data were analyzed using the Wilcoxon Test because the data were not normally distributed. The results of the analysis showed that between the pretest and posttest showed N : 11, Mean: 10.50 and Sum: 115,50. This shows that there is a decrease in the pretest and posttest scores of 11 students with an average decrease in the pretest and posttest scores.